Héraclite : l’injure et la moquerie philosophiques - Pierre Destrée (Cahiers Mondes Anciens, 2014)
Contrary to the traditional view of a Heracleitus who doesn't laugh or make laugh, Heracleitus must be considered, I claim, as a satirist philosopher. Several of his fragments are to be read from the background of iambic poetry. Heracleitus makes a philosophical usage of laughter: these fragments are meant to provoke people - his potential audience -, and make them think.